Citation Analisis as a Tool of Library Collections Evaluation - Hayati, Nurul (Universitas Airlangga, 2016)
This paper discusses about citation analisis as a tool that can be used in performing library collection evaluation. The discussion include source, scope and analysis parameter, literature character, and the analysis advantage of citation. Through this citation analysis, it can be known the growth and the development of science in certain subject. In citation analysis, it also can be described relation between parts or all documents cited with citing documents. So, it can be counted how many works cited by authors. For libraries, the result of citation analysis becomes consideration in making collection development policy. It is recommended that the library pays attention to the collection of the researches that are based on the citation analysis and uses them as collection evaluation tool. Other than that, the library should use the researches that are based on the citation analysis as the consideration in making the policy of collection development.Â